The Revenge of Geography - V. Ia. Belokrenitsky (Сравнительная политика, 2016)
This author discussed the prominent book of American journalist and expert Robert D. Kaplan in the light of the recent publication of its Russian translation: [Kaplan R. Mest’ geografi i (The revenge of geography) / Transl. by M. Kotov. Moscow: Ko-Libri, 2015. P.277].